2013
DOI: 10.1111/mmi.12404
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and nucleoid localization are independently conserved functions in bacteriophage terminal proteins

Abstract: SummaryBacteriophage terminal proteins (TPs) prime DNA replication and become covalently linked to the DNA 5′-ends. In addition, they are DNA-binding proteins that direct early organization of phage DNA replication at the bacterial nucleoid and, unexpectedly, contain nuclear localization signals (NLSs), which localize them to the nucleus when expressed in mammalian cells. In spite of the lack of sequence homology among the phage TPs, these three properties share some common features, suggesting a possible evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Importantly, K27A and K25A/K27A TP mutants, affected in nucleoid localization, were impaired in recruiting the DNA polymerase to the bacterial nucleoid and did not complement the infection with a sus3 (91) mutant phage, being defective in providing an efficient viral DNA replication in vivo . It is worth to mention that, when expressed in the non‐host bacterium E. coli , TP N‐terminal mutants R19A and K32/33/34A fusioned to YFP localized at the nucleoid in the same manner as the wild‐type TP did, whereas K27A and K25/27A mutant TPs were found to localize in a spotted pattern at the nucleoid (Redrejo‐Rodríguez et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, K27A and K25A/K27A TP mutants, affected in nucleoid localization, were impaired in recruiting the DNA polymerase to the bacterial nucleoid and did not complement the infection with a sus3 (91) mutant phage, being defective in providing an efficient viral DNA replication in vivo . It is worth to mention that, when expressed in the non‐host bacterium E. coli , TP N‐terminal mutants R19A and K32/33/34A fusioned to YFP localized at the nucleoid in the same manner as the wild‐type TP did, whereas K27A and K25/27A mutant TPs were found to localize in a spotted pattern at the nucleoid (Redrejo‐Rodríguez et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It was also found that some nucleoid associated proteins can play role in gene regulation and horizontal gene transfer in enterobacteria 27 . It was also found that some protein can have independent nuclear and nucleoid localization functions 28 . In this study it was predicted that it has nucleic acid binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…The Bam35 TP mutants were obtained by directed mutagenesis using the pT7-7::B35TP plasmid as the template, the oligonucleotides indicated in Supplementary Table S1 and the Pfu DNA polymerase (New England Biolabs). The YFP fusion to the Bam35 TP (YFPTP) was produced from a vector, obtained by cloning the TP PCR product into the EcoRI/BamHI sites of pStrep-YFP plasmid (33). The resulting vector, pStrep-YFP::B35TP, was used to express a N-terminal strep-tagged YFP fusion terminal protein (YFPTP).…”
Section: Methodsmentioning
confidence: 99%